The role of slab geometry in the exhumation of cordilleran-type orogens and their forelands: Insights from northern Patagonia - Genge, Marie C. (2021)
In cordilleran-type orogens, subduction geometry exerts a fundamental control on the tectonic behavior of the overriding plate. An integrated low-temperature, large thermochronological data set is used in this study to investigate the burial and exhumation history of the overriding plate in northern Patagonia (40°–45°S). Thermal inverse modeling allowed us to establish that a ~2.5–4-km-thick section originally overlaid the Jurassic–Lower Cretaceous successions deposited in half-graben systems that are presently exposed in the foreland. Removal of the sedimentary cover started in the late Early Cretaceous. This was coeval with an increase of the convergence rate and a switch to a westward absolute motion of the South American Plate that was accompanied by shallowing of the subducting slab. Unroofing was probably further enhanced by Late Cretaceous to early Paleogene opening of a slab window beneath the overriding plate. Following a tectonically quiescent period, renewed exhumation occurred in the orogen during relatively fast Neogene plate convergence. However, even the highly sensitive apatite (U-Th)/He thermochronometer does not record any coeval cooling in the foreland. The comparison between Late Cretaceous and Neogene exhumation patterns provides clear evidence of the fundamental role played by inter-plate coupling associated with shallow slab configurations in controlling plate-scale deformation. Our results, besides highlighting for the first time how the whole northern Patagonia foreland was affected by an exhumation of several kilometers since the Late Cretaceous, provide unrivalled evidence of the link between deep geodynamic processes affecting the slab and the modes and timing of unroofing of different sectors of the overriding plate.